Attention to climate change and downside risk: Evidence from China. Issue 5 (25th June 2022) - Chen, Xing; Chen, Xian; Xu, Longhao; Wen, Fenghua
Abstract: We explore the role of public climate attention, captured by the Baidu search volume index, in the downside risk. Using 45 keywords from five perspectives related to climate change, we construct a public climate attention index in China. We find a positive and significant relationship between climate attention and downside risk at the market‐level and firm‐level. Moreover, the risk‐increase effect of climate attention becomes more prominent for state‐owned and high‐carbon‐emission firms. Further analysis shows that excellent sustainable performance can moderate the adverse effect of rising climate attention, while the major climate disasters exacerbate the effect. Overall, our findings shed additional light on the important role of collective climate beliefs in corporate risk management and investor decision‐making.